2021
DOI: 10.1007/s43390-021-00315-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the pain and disability of patients with adult spinal deformity

Abstract: Purpose To evaluate the pain and functional effect of the COVID-19 pandemic on patients with ASD reflected by their response to SRS-22, ODI, and SF-36 questionnaires. Methods Patients who had stable pain and functional outcome scores over the preceding 2 years were enrolled in a local prospectively collected adult spinal deformity (ASD) database. A reanalysis of their SRS22, ODI and SF-36 data 14 days into confinement were compared to their last pre-confinement scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In terms of functioning, our data are consistent with those of other studies, namely, lockdown did not negatively affect patients, as shown by the SRS-22 and SF-12. [ 29 ] However, we cannot say the same for psychological status, since, although statistically significant differences were not recorded in the psychological dimension of SRS-22 or the SF-12, the GDS revealed that more than half of the study population is at risk of depression (GDS > 5), which was more frequent in women and patients who underwent surgery. This finding is most likely due to the strict lockdown measures.…”
Section: Discussionmentioning
confidence: 88%
“…In terms of functioning, our data are consistent with those of other studies, namely, lockdown did not negatively affect patients, as shown by the SRS-22 and SF-12. [ 29 ] However, we cannot say the same for psychological status, since, although statistically significant differences were not recorded in the psychological dimension of SRS-22 or the SF-12, the GDS revealed that more than half of the study population is at risk of depression (GDS > 5), which was more frequent in women and patients who underwent surgery. This finding is most likely due to the strict lockdown measures.…”
Section: Discussionmentioning
confidence: 88%
“…In our study, 31.4% of the participants claimed the pandemic had affected them in some manner. A survey of postoperative patients with adult spinal deformity reported that confinement during the pandemic had no effect on SRS-22, although a negative effect in relation to ODI was detected [ 18 ]. Our study results indicated no correlation between the impact of the COVID-19 pandemic and ODI deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it would be callous to discount the effect of chronic disability on mental health, and refusal to match patients may lead to our hypothesized findings but could also be a result of significant confounding. Of note, in a study of adult spinal deformity patients, Kieser et al (2021) 27 demonstrated the effects of a 14-day quarantine on baseline PROs to be variable but reported significantly worsened ODI scores. Cohen and colleagues (2021) conducted a study quite similar to ours, except studying the “Hand-Wrist Study Cohort” as opposed to spine patients.…”
Section: Discussionmentioning
confidence: 99%